Penyuluhan Peningkatan Kualitas Air Bersih Melalui Pelatihan Pembuatan Filter Air Sederhana di Desa Pekubuan - Srg, Lailatun Nur Kamalia; Al Ghifari, Muhammad; Aziz, Nurul Azmi; Putri, Octa Yulanda (Civiliza Publishing, 2024)
The water category in one of the areas, namely Langkat Regency, Tanjung Pura District, Pekubuan Village, is said to be unclear and murky so it can be said that it does not meet cleanliness standards. To overcome this problem, simple and cheap technology for water filtration can be a practical solution for the people of Pekubuan Village, namely by using a simple water filter that uses natural materials such as sand, charcoal, palm fiber and gravel. This research aims to evaluate the effectiveness of training in making simple water filters in improving the quality of clean water that can be consumed by the community. This research uses qualitative methods by conducting outreach, outreach, practice of making simple water filtration and evaluation. The results obtained from the training in making simple water filters were to increase the insight of the people of Pekubuan Village that water that is cloudy and unfit for consumption can be filtered in a simple way to become clean water.